Not a suicide pact: the constitution in a time of national emergency - Posner, Richard A. (Inalienable rights series, 2006)
How are constitutional rights created? -- How does national security shape constitutional rights? -- Rights against detention -- Rights against brutal interrogation, and against searches and seizures -- The right of free speech, with a comment on "profiling" -- Rights of privacy